The EFEKTIVITAS EKSTRAK ETANOL DAUN BANDOTAN (Ageratum conyzoides) TERHADAP Salmonella enterica serovar typhimurium SECARA IN VITRO: : - daniel, daniel daniel; admi, masda; putri, anggun bellia; helmi, teuku zahrial; wardhani, lailia dwi Kusuma (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Bandotan leaves (Ageratum conyzoides) are one of the traditional medicinal plants that are trusted empirically by the community to treat various diseases. Several studies report the potential of bandotan leaves as an antibacterial because they contain the chemical compounds trepanoids, flavonoids, alkaloids, essential oils, and tannins. This study aims to determine the effectiveness of bandotan leaves on the growth of Salmonella enterica serovar typhimurium bacteria in vitro. This research used the Kirby Bauer disk diffusion method with the antibiotic chloramphenicol as a positive control, CMC 1% as a negative control, and an ethanol extract of bandotan leaves with concentrations of 25%, 50%, and 75%. Re-identification of bacteria was carried out using Gram staining, and effectiveness testing was carried out on Mueller Hinton Agar (MHA) media. The results of the study on Gram staining showed uniform morphological characteristics of Salmonella enterica serovar Typhimurium bacteria and the diameter of the inhibition zone formed at concentrations of bandotan leaf ethanol extract of 25% (8.02 mm ± 0.41), 50% (8.37mm ± 0.69) and 75% (8.78mm ± 0.78). It can be concluded that the ethanol extract of bandotan leaves at concentrations of 25%, 50%, and 75% has a weak category of inhibitory activity against the growth of Salmonella enterica serovar Typhimurium bacteria in vitro.